A PO composite membrane and preparation method thereof
Through the use of the modified coating liquid, the hydrophilicity and adhesion of the PO film are improved, and the problem of poor mist removal and droplet properties of the PO film is solved, and the excellent anti-fog performance and high adhesion of the PO composite film are achieved, which improves the photosynthesis efficiency and disease prevention and control capabilities of the crops.
Patent Information
- Application Number
- CN202411268133.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The PO film has poor mist and droplet properties, especially in winter, which leads to a decrease in the light transmittance of the greenhouse film and the occurrence of vegetable diseases.
By modifying the coating liquid, its hydrophilicity and adhesion are increased, and raw materials such as aluminum sol, modified hyperbranched polymer and modified chitosan are used to form a PO composite film with excellent droplet anti-fog performance.
The anti-fog performance and adhesion of the PO composite film are improved, the surface tension of water is reduced, the occurrence of water droplets is reduced, and the light transmittance of the film and the photosynthesis efficiency of crops is significantly improved.
Smart Images

Figure BDA0005037800410000131
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite membranes, and in particular to a PO composite membrane and a preparation method thereof. Background Art
[0002] PO film is a new type of agricultural film, mainly including base film and coating liquid. The base film is made by adding functional masterbatch to polyethylene materials such as linear low-density polyethylene (LLDPE) and low-density polyethylene (LDPE), stirring with a high-speed mixer, and then extruding and pelletizing with a twin-screw extruder; while the coating liquid is mixed with film-forming agent, surfactant and other functional additives, and then applied on the surface of the base film to form a coating layer. PO film is an upgraded product of EVA film, which has brought revolutionary improvements to traditional agricultural greenhouse films. This high-tech coating product has the advantages of high light transmittance, strong tensile strength, and aging resistance. It is suitable for a variety of agricultural scenarios, such as greenhouse planting, orchard covering, etc., especially in the cultivation of fruits and vegetables that require high temperatures, which can significantly improve yield and quality.
[0003] However, the anti-fogging and anti-drip performance of PO membrane is poor, especially in winter, the water produced by the respiration of crops gathers on the greenhouse film to form water droplets, causing the external incident light to be reflected or refracted, reducing the light transmittance of the greenhouse film, affecting the photosynthesis of crops, and at the same time, the water droplets drip on the leaves of crops, forming a water film on the leaves, creating conditions for the infection and growth of pathogens, and causing vegetable diseases. Therefore, it is necessary to modify the coating liquid used for PO membrane to improve the hydrophilicity of the film layer formed by the coating liquid, thereby reducing the surface tension of water, improving the dripping and anti-fogging performance of PO membrane, and at the same time, it is necessary to improve the adhesion of the coating liquid on the surface of the base film to reduce the reduction of the coating liquid film layer caused by long-term dripping of water droplets. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a PO composite membrane and a preparation method thereof.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A PO composite film is formed by co-extruding an inner layer, a sub-outer layer and an outer layer to form a base film, and the base film is then uniformly coated with a coating liquid; in the base film, the thickness of the inner layer: the thickness of the sub-outer layer: the thickness of the outer layer = 1:3-5:1; the inner layer, the sub-outer layer and the outer layer are respectively made of the following raw materials in mass percentage:
[0007] Inner layer: 20%-25% low-density polyethylene, 60%-70% linear low-density polyethylene, 10%-20% antistatic masterbatch;
[0008] Furthermore, the antistatic masterbatch is made of the following raw materials in mass percentage, namely: 75%-85% low-density polyethylene, 15%-25% antistatic agent and 1%-2% antioxidant are mixed, melted at high temperature and pelletized;
[0009] Second outer layer: 20%-25% low density polyethylene, 40%-70% metallocene polyethylene, 10%-20% hydrotalcite masterbatch;
[0010] Furthermore, the hydrotalcite masterbatch is made of the following raw materials in percentage by mass: 70%-80% low-density polyethylene, 15%-30% hydrotalcite, 1%-2% antioxidant and 2%-4% hindered amine light stabilizer are mixed, melted at high temperature and pelletized;
[0011] Outer layer: 40%-50% metallocene polyethylene, 15%-25% high-density polyethylene, 30%-40% antioxidant masterbatch;
[0012] Furthermore, the antioxidant masterbatch is made of the following raw materials in the following mass percentages, namely: 30%-40% low-density polyethylene, 40%-60% linear low-density polyethylene, 1%-2% antioxidant, 3%-6% hindered amine light stabilizer, 2%-4% ultraviolet absorber and 1%-3% antistatic agent, which are mixed, melted at high temperature and pelletized.
[0013] The coating liquid comprises the following raw materials in parts by weight: 25-35 parts of aluminum sol, 5-8 parts of modified hyperbranched polymer, 2-4 parts of polyvinyl pyrrolidone, 1-3 parts of sodium lauryl sulfate, 5-7 parts of polyacrylic acid resin, 4-6 parts of modified chitosan, and 45-55 parts of deionized water;
[0014] The modified hyperbranched polymer is prepared by the following steps:
[0015] Step A1, adding methyltrimethoxysilane and dimethyldiethoxysilane to an ethanol solution, stirring at a speed of 400-600 rpm for 1.5-2.5 hours, then slowly adding trifluoropropane trimethoxysilane and tetraethyl orthosilicate and continuing stirring for 1-2 hours, adding 10wt% ammonia water and stopping stirring, transferring to a 60°C water bath and standing for 30-50 minutes, centrifuging, washing, and drying to obtain silicone microspheres;
[0016] Step A2, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are uniformly mixed in an N,N-dimethylformamide aqueous solution, and then silicone microspheres are added, reacted under nitrogen at 80-90° C. for 3-4 hours, tetrahydrofuran is added and stirred for 10 minutes, washed and dried to obtain a hyperbranched polymer precursor;
[0017] Step A3, mixing the hyperbranched polymer precursor and sodium hydroxide in ethanol, adding dopamine hydrochloride and stirring to react for 2-3 hours, distilling under reduced pressure, filtering, washing and drying to obtain a modified hyperbranched polymer;
[0018] Furthermore, in step A1, the dosage ratio of methyltrimethoxysilane, dimethyldiethoxysilane, trifluoropropanetrimethoxysilane, tetraethyl orthosilicate, ethanol solution and ammonia water is 0.05-0.15 mol: 0.03-0.06 mol: 0.01-0.03 mol: 0.08-0.12 mol: 200 mL: 1-3 mL, and the volume ratio of ethanol to deionized water in the ethanol solution is 1:1;
[0019] Furthermore, in step A2, the dosage ratio of trimethylolpropane triglycidyl ether, tetrabutylammonium bromide, N,N-dimethylformamide aqueous solution, silicone microspheres and tetrahydrofuran is 0.01-0.03 mol: 0.0005-0.0015 mol: 100 mL: 1-3 g: 10 mL, and the volume ratio of N,N-dimethylformamide and deionized water in the N,N-dimethylformamide aqueous solution is 4:1;
[0020] Further, in step A3, the ratio of the hyperbranched polymer precursor, sodium hydroxide, ethanol and dopamine hydrochloride is 1-3 g: 0.01-0.02 g: 50 mL: 0.5-2 g;
[0021] The modified chitosan comprises the following steps of preparation:
[0022] Step B1, adding chitosan to a 3wt% glacial acetic acid solution and stirring for 30min, adding 10mL of anhydrous ethanol and stirring for 10min, heating to 35-45°C, adding 2-4wt% glyoxal solution and stirring for 1-2h, centrifuging and washing, redispersing in 100mL of anhydrous ethanol, adding N,N-dimethylethylenediamine, and reacting at 40-50°C for 2-3h, centrifuging and drying to obtain pre-treated chitosan;
[0023] Step B2, dispersing the pretreated chitosan in ethanol, heating to 45°C, slowly adding 1-chlorododecane, stirring for 8-12h, standing for 12h, centrifuging, rotary evaporating, and drying to obtain modified chitosan;
[0024] Further, in step B1, the amount ratio of chitosan, glacial acetic acid solution, glyoxal solution and N,N-dimethylethylenediamine is 1-3 g: 10-20 mL: 10-20 mL: 0.5-2 mL;
[0025] Furthermore, in step B2, the usage ratio of pre-treated chitosan, ethanol and 1-chlorododecane is 1-3 g: 50 mL: 0.5-2 mL.
[0026] A method for preparing a PO composite membrane comprises the following steps:
[0027] Step S1, weighing the raw materials according to the mass percentage, respectively putting the raw materials of the outer layer, the sub-outer layer and the inner layer of the base film into the corresponding production barrels, blow-molding by a three-layer co-agent blow-molding unit, and then pulling and corona treating to obtain the base film;
[0028] Step S2, weighing the raw materials by weight, mixing and stirring the modified hyperbranched polyester, polyvinyl pyrrolidone, sodium lauryl sulfate and modified chitosan at 25-30° C. for 30 minutes, adding aluminum sol and continuing to stir for 40-60 minutes to form a mixed solution 1; then mixing and stirring the polyacrylic acid resin and deionized water to form a mixed solution 2; finally, slowly adding the mixed solution 2 to the mixed solution 1, and continuing to stir for 30-50 minutes to obtain a coating solution;
[0029] Step S3, uniformly coating the coating liquid on the surface of the base film, with a film thickness of 0.1-0.2 mm, drying, and rolling up to obtain a PO composite film.
[0030] Beneficial effects of the present invention:
[0031] The PO composite membrane prepared by the present invention comprises a base membrane and a coating liquid; wherein the base membrane is formed by co-extrusion of an inner layer, a sub-outer layer and an outer layer, and the coating liquid is prepared by mixing raw materials such as aluminum sol, modified hyperbranched polymer, and modified chitosan; after the base membrane is coated with the coating liquid, a composite membrane is obtained, which has excellent adhesion, hydrophilicity, and dripping and anti-fogging properties.
[0032] In the modified hyperbranched polymer, methyltrimethoxysilane, dimethyldiethoxysilane, trifluoropropane trimethoxysilane and tetraethyl orthosilicate are first used as raw materials to synthesize silicone microspheres; then, the epoxy group in trimethylolpropane triglycidyl ether is reacted with the hydroxyl group in the silicone microsphere to produce a hyperbranched polymer precursor; finally, the epoxy group in the hyperbranched polymer precursor is reacted with the amino group in dopamine hydrochloride to synthesize the modified hyperbranched polymer. The modified hyperbranched polymer is introduced into the coating liquid as a polyhydroxy nonionic surfactant. It can not only utilize the polyhydroxy structure to improve the hydrophilicity of the composite membrane surface, but also utilize its unique hyperbranched structure to embed the core layer silicone microspheres into the membrane structure produced after coating, while the branched structure of the shell layer can be spread out in the coating liquid to form a network structure, further enhancing the hydrophilicity of the composite membrane surface. The increase in hydrophilicity reduces the surface tension of water. The reduction in the surface tension of water is conducive to the expansion of water droplets on the membrane surface and the convergence of adjacent water droplets to form a water flow, thereby allowing the droplets on the membrane surface to flow away quickly, avoiding the occurrence of water droplets, and thereby improving the drip anti-fog performance of the composite membrane; in addition, the dopamine introduced at its end contains a catechol structure, and the catechol structure not only has excellent hydrophilicity, but also can interact with the surface of the base membrane, including hydrogen bonding, hydrophobic interaction, etc., thereby improving the adhesion between the coating liquid and the base membrane.
[0033] In the modified chitosan, glacial acetic acid is first used to treat chitosan to expose more amino groups in chitosan, and then ethylene glycol is used as a cross-linking agent to introduce a tertiary amine structure into chitosan, and finally a chlorinated hydrocarbon and a tertiary amine are reacted to obtain the modified chitosan; after the modified chitosan is introduced into the coating liquid, it can not only significantly improve the adhesion of the coating liquid to the base film, but also work synergistically with the surfactant (modified hyperbranched polyester, polyvinyl pyrrolidone and sodium lauryl sulfate) to further improve the hydrophilicity of the composite film surface and reduce the surface tension of water; among them, the modified chitosan can be bonded to the surface of the composite film. The synergistic effect or physical adsorption provides a strong bonding force between the coating liquid and the base film, enhances the adhesion of the coating film, and effectively reduces the peeling phenomenon of the coating film caused by the external environment, making it not easy to peel off and resistant to friction; the quaternary ammonium salt structure introduced in the modified chitosan can not only improve the hydrophilicity of the composite film, but also give the surface of the composite film a certain antistatic property, thereby reducing the generation of static electricity on the surface of the composite film; in addition, chitosan can also be used as an emulsifier to help the coating liquid form a uniform coating on the polyolefin film, further improving the adhesion and waterproof and oil-proof properties. DETAILED DESCRIPTION
[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Example 1
[0036] The modified hyperbranched polymer is prepared by the following steps:
[0037] Step A1, add 0.05 mol of methyltrimethoxysilane and 0.03 mol of dimethyldiethoxysilane to 200 mL of ethanol solution, and stir at 400 rpm for 1.5 h, then slowly add 0.01 mol of trifluoropropanetrimethoxysilane and 0.08 mol of tetraethyl orthosilicate, continue stirring for 1 h, add 1 mL of 10 wt% ammonia water and stop stirring, transfer to a 60° C. water bath and let stand for 30 min, centrifuge, wash, and dry to obtain organosilicon microspheres, wherein the volume ratio of ethanol to deionized water in the ethanol solution is 1:1;
[0038] Step A2, 0.01 mol of trimethylolpropane triglycidyl ether and 0.0005 mol of tetrabutylammonium bromide were mixed evenly in 100 mL of N, N-dimethylformamide aqueous solution, and then 1 g of organosilicon microspheres were added, and the mixture was reacted under nitrogen at 80° C. for 3 h, and 10 mL of tetrahydrofuran was added and stirred for 10 min, and then washed and dried to obtain a hyperbranched polymer precursor. The volume ratio of N, N-dimethylformamide to deionized water in the N, N-dimethylformamide aqueous solution was 4:1;
[0039] Step A3, 1 g of the hyperbranched polymer precursor and 0.01 g of sodium hydroxide were mixed evenly in 50 mL of ethanol, and 0.5 g of dopamine hydrochloride was added and stirred for 2 h, and the mixture was distilled under reduced pressure, filtered, washed and dried to obtain a modified hyperbranched polymer.
[0040] The modified chitosan comprises the following steps for preparation:
[0041] Step B1, add 1g chitosan to 10mL 3wt% glacial acetic acid solution and stir for 30min, add 10mL anhydrous ethanol and stir for 10min, heat to 35°C, add 10mL 2wt% glyoxal solution and stir for 1h, centrifuge and wash, redisperse in 100mL anhydrous ethanol, add 0.5mL N,N-dimethylethylenediamine, react at 40°C for 2h, centrifuge and dry to obtain pre-treated chitosan;
[0042] Step B2, disperse 1 g of pretreated chitosan in 50 mL of ethanol, heat to 45°C, slowly drop 0.5 mL of 1-chlorododecane, stir to react for 8 h, let stand for 12 h, centrifuge, rotary evaporate, and dry to obtain modified chitosan.
[0043] Example 2
[0044] The modified hyperbranched polymer is prepared by the following steps:
[0045] Step A1, add 0.1 mol of methyltrimethoxysilane and 0.045 mol of dimethyldiethoxysilane to 200 mL of ethanol solution, and stir at a speed of 500 rpm for 2 h, then slowly add 0.02 mol of trifluoropropanetrimethoxysilane and 0.1 mol of tetraethyl orthosilicate, continue stirring for 1.5 h, add 2 mL of 10 wt% ammonia water, stop stirring, transfer to a 60° C. water bath and let stand for 40 min, centrifuge, wash, and dry to obtain organosilicon microspheres, wherein the volume ratio of ethanol to deionized water in the ethanol solution is 1:1;
[0046] Step A2, 0.02 mol of trimethylolpropane triglycidyl ether and 0.001 mol of tetrabutylammonium bromide are mixed evenly in 100 mL of N, N-dimethylformamide aqueous solution, and then 1-3 g of organosilicon microspheres are added, reacted under nitrogen at 85° C. for 3.5 h, 10 mL of tetrahydrofuran is added, stirred for 10 min, washed, and dried to obtain a hyperbranched polymer precursor, wherein the volume ratio of N, N-dimethylformamide to deionized water in the N, N-dimethylformamide aqueous solution is 4:1;
[0047] Step A3, 2 g of the hyperbranched polymer precursor and 0.015 g of sodium hydroxide were mixed evenly in 50 mL of ethanol, and 1 g of dopamine hydrochloride was added and stirred for 2.5 h, and the mixture was distilled under reduced pressure, filtered, washed and dried to obtain a modified hyperbranched polymer.
[0048] The modified chitosan comprises the following steps for preparation:
[0049] Step B1, add 2g chitosan to 15mL 3wt% glacial acetic acid solution and stir for 30min, add 10mL anhydrous ethanol and stir for 10min, heat to 40°C, add 15mL 3wt% glyoxal solution and stir for 1.5h, centrifuge and wash, redisperse in 100mL anhydrous ethanol, add 1mL N,N-dimethylethylenediamine, react at 45°C for 2.5h, centrifuge and dry to obtain pre-treated chitosan;
[0050] Step B2, disperse 2 g of pretreated chitosan in 50 mL of ethanol, heat to 45° C., slowly drop 1 mL of 1-chlorododecane, stir to react for 10 h, let stand for 12 h, centrifuge, rotary evaporate, and dry to obtain modified chitosan.
[0051] Example 3
[0052] The modified hyperbranched polymer is prepared by the following steps:
[0053] Step A1, add 0.15 mol of methyltrimethoxysilane and 0.06 mol of dimethyldiethoxysilane to 200 mL of ethanol solution, and stir at 600 rpm for 2.5 h, then slowly add 0.03 mol of trifluoropropanetrimethoxysilane and 0.12 mol of tetraethyl orthosilicate and continue stirring for 2 h, add 3 mL of 10 wt% ammonia water and stop stirring, transfer to a 60° C. water bath and let stand for 50 min, centrifuge, wash and dry to obtain organosilicon microspheres, wherein the volume ratio of ethanol to deionized water in the ethanol solution is 1:1;
[0054] Step A2, 0.03 mol of trimethylolpropane triglycidyl ether and 0.0015 mol of tetrabutylammonium bromide were mixed uniformly in 100 mL of N, N-dimethylformamide aqueous solution, and then 3 g of organosilicon microspheres were added, and the mixture was reacted under nitrogen at 90° C. for 4 h, 10 mL of tetrahydrofuran was added and stirred for 10 min, and then washed and dried to obtain a hyperbranched polymer precursor, wherein the volume ratio of N, N-dimethylformamide to deionized water in the N, N-dimethylformamide aqueous solution was 4:1;
[0055] Step A3, 3 g of the hyperbranched polymer precursor and 0.02 g of sodium hydroxide were mixed evenly in 50 mL of ethanol, and 2 g of dopamine hydrochloride was added and stirred for 3 h, and the mixture was distilled under reduced pressure, filtered, washed and dried to obtain a modified hyperbranched polymer.
[0056] The modified chitosan comprises the following steps for preparation:
[0057] Step B1, add 3g chitosan to 20mL 3wt% glacial acetic acid solution and stir for 30min, add 10mL anhydrous ethanol and stir for 10min, heat to 45°C, add 20mL 4wt% glyoxal solution and stir for 2h, centrifuge and wash, redisperse in 100mL anhydrous ethanol, add 2mL N,N-dimethylethylenediamine, react at 50°C for 3h, centrifuge and dry to obtain pre-treated chitosan;
[0058] Step B2, disperse 3 g of pretreated chitosan in 50 mL of ethanol, heat to 45° C., slowly drop 2 mL of 1-chlorododecane, stir to react for 12 h, let stand for 12 h, centrifuge, rotary evaporate, and dry to obtain modified chitosan.
[0059] Example 4
[0060] A PO composite film is formed by co-extruding an inner layer, a sub-outer layer and an outer layer to form a base film, and the base film is then uniformly coated with a coating liquid; in the base film, the thickness of the inner layer: the thickness of the sub-outer layer: the thickness of the outer layer = 1:3:1; the inner layer, the sub-outer layer and the outer layer are respectively made of the following raw materials in mass percentage:
[0061] Inner layer: 20% low-density polyethylene, 70% linear low-density polyethylene, 10% antistatic masterbatch; the antistatic masterbatch is made of the following raw materials in percentage by mass, namely: 75% low-density polyethylene, 24% antistatic agent B-902 and 1% antioxidant 1010 are mixed, melted at high temperature and pelletized;
[0062] Second outer layer: 20% low-density polyethylene, 70% metallocene polyethylene, 10% hydrotalcite masterbatch; the hydrotalcite masterbatch is made of the following raw materials in percentage by mass, namely: 70% low-density polyethylene, 25% hydrotalcite, 1% antioxidant 1010 and 4% hindered amine light stabilizer XT100 are mixed, melted at high temperature and pelletized;
[0063] Outer layer: 50% metallocene polyethylene, 20% high-density polyethylene, 30% antioxidant masterbatch. The antioxidant masterbatch is made of the following raw materials in percentage by mass: 33% low-density polyethylene, 60% linear low-density polyethylene, 1% antioxidant 1010, 3% hindered amine light stabilizer XT100, 2% ultraviolet absorber uv-326 and 1% antistatic agent B-902 are mixed, melted at high temperature and pelletized;
[0064] The coating liquid comprises the following raw materials in parts by weight: 25 parts of aluminum sol, 5 parts of modified hyperbranched polymer prepared in Example 1, 2 parts of polyvinyl pyrrolidone, 1 part of sodium lauryl sulfate, 5 parts of polyacrylic acid resin, 4 parts of modified chitosan prepared in Example 1, and 45 parts of deionized water;
[0065] A method for preparing a PO composite membrane comprises the following steps:
[0066] Step S1, weighing the raw materials according to the mass percentage, respectively putting the raw materials of the outer layer, the sub-outer layer and the inner layer of the base film into the corresponding production barrels, blow-molding by a three-layer co-agent blow-molding unit, and then pulling and corona treating to obtain the base film;
[0067] Step S2, weighing the raw materials by weight, mixing the modified hyperbranched polyester prepared in Example 1, polyvinyl pyrrolidone, sodium lauryl sulfate and the modified chitosan prepared in Example 1 at 25° C. and stirring for 30 minutes, adding aluminum sol and continuing stirring for 40 minutes to form a mixed solution 1; then mixing the polyacrylic acid resin and deionized water and stirring them uniformly to form a mixed solution 2; finally, slowly adding the mixed solution 2 into the mixed solution 1 and continuing stirring for 30 minutes to obtain a coating solution;
[0068] Step S3, uniformly coating the coating liquid on the surface of the base film, with a film thickness of 0.1 mm, drying, and rolling up to obtain a PO composite film.
[0069] Example 5
[0070] A PO composite film is formed by co-extruding an inner layer, a sub-outer layer and an outer layer to form a base film, and the base film is then uniformly coated with a coating liquid; in the base film, the thickness of the inner layer: the thickness of the sub-outer layer: the thickness of the outer layer = 1:4:1; the inner layer, the sub-outer layer and the outer layer are respectively made of the following raw materials in mass percentage:
[0071] Inner layer: 25% low-density polyethylene, 60% linear low-density polyethylene, 15% antistatic masterbatch. The antistatic masterbatch is made of the following raw materials in percentage by mass: 78% low-density polyethylene, 20% antistatic agent B-902 and 2% antioxidant 1010 are mixed, melted at high temperature and pelletized;
[0072] Second outer layer: 25% low-density polyethylene, 60% metallocene polyethylene, 15% hydrotalcite masterbatch, the hydrotalcite masterbatch is made of the following raw materials in percentage by mass, namely: 70% low-density polyethylene, 25% hydrotalcite, 2% antioxidant 1010 and 3% hindered amine light stabilizer XT100 are mixed, melted at high temperature and pelletized;
[0073] Outer layer: 45% metallocene polyethylene, 20% high-density polyethylene, 35% antioxidant masterbatch. The antioxidant masterbatch is made of the following raw materials in percentage by mass: 38% low-density polyethylene, 50% linear low-density polyethylene, 2% antioxidant 1010, 5% hindered amine light stabilizer XT100, 3% ultraviolet absorber uv-326 and 2% antistatic agent B-902 are mixed, melted at high temperature and pelletized;
[0074] The coating liquid comprises the following raw materials in parts by weight: 30 parts of aluminum sol, 7 parts of modified hyperbranched polymer prepared in Example 2, 3 parts of polyvinyl pyrrolidone, 2 parts of sodium lauryl sulfate, 6 parts of polyacrylic acid resin, 5 parts of modified chitosan prepared in Example 2, and 50 parts of deionized water;
[0075] A method for preparing a PO composite membrane comprises the following steps:
[0076] Step S1, weighing the raw materials according to the mass percentage, respectively putting the raw materials of the outer layer, the sub-outer layer and the inner layer of the base film into the corresponding production barrels, blow-molding by a three-layer co-agent blow-molding unit, and then pulling and corona treating to obtain the base film;
[0077] Step S2, weighing the raw materials by weight, mixing the modified hyperbranched polyester prepared in Example 2, polyvinyl pyrrolidone, sodium lauryl sulfate and the modified chitosan prepared in Example 2 at 30° C. and stirring for 30 minutes, adding aluminum sol and continuing to stir for 50 minutes to form a mixed solution 1; then mixing the polyacrylic acid resin and deionized water and stirring evenly to form a mixed solution 2; finally, slowly adding the mixed solution 2 into the mixed solution 1, and continuing to stir for 40 minutes to obtain a coating solution;
[0078] Step S3, uniformly coating the coating liquid on the surface of the base film, the film layer thickness is 0.15 mm, drying, and rolling up to obtain a PO composite film.
[0079] Example 6
[0080] A PO composite film is formed by co-extruding an inner layer, a sub-outer layer and an outer layer to form a base film, and the base film is then uniformly coated with a coating liquid; in the base film, the thickness of the inner layer: the thickness of the sub-outer layer: the thickness of the outer layer = 1:5:1; the inner layer, the sub-outer layer and the outer layer are respectively made of the following raw materials in mass percentage:
[0081] Inner layer: 20% low-density polyethylene, 60% linear low-density polyethylene, 20% antistatic masterbatch. The antistatic masterbatch is made of the following raw materials in percentage by mass: 75% low-density polyethylene, 23% antistatic agent B-902 and 2% antioxidant 1010 are mixed, melted at high temperature and pelletized;
[0082] Second outer layer: 20% low-density polyethylene, 60% metallocene polyethylene, 20% hydrotalcite masterbatch, the hydrotalcite masterbatch is made of the following raw materials in percentage by mass, namely: 70% low-density polyethylene, 24% hydrotalcite, 2% antioxidant 1010 and 4% hindered amine light stabilizer XT100 are mixed, melted at high temperature and pelletized;
[0083] Outer layer: 45% metallocene polyethylene, 15% high-density polyethylene, 40% antioxidant masterbatch. The antioxidant masterbatch is made of the following raw materials in percentage by mass: 35% low-density polyethylene, 50% linear low-density polyethylene, 2% antioxidant 1010, 6% hindered amine light stabilizer XT100, 4% ultraviolet absorber uv-326 and 3% antistatic agent B-902 are mixed, melted at high temperature and pelletized;
[0084] The coating liquid comprises the following raw materials in parts by weight: 35 parts of aluminum sol, 8 parts of modified hyperbranched polymer prepared in Example 3, 4 parts of polyvinyl pyrrolidone, 3 parts of sodium lauryl sulfate, 7 parts of polyacrylic acid resin, 6 parts of modified chitosan prepared in Example 3, and 55 parts of deionized water;
[0085] A method for preparing a PO composite membrane comprises the following steps:
[0086] Step S1, weighing the raw materials according to the mass percentage, respectively putting the raw materials of the outer layer, the sub-outer layer and the inner layer of the base film into the corresponding production barrels, blow-molding by a three-layer co-agent blow-molding unit, and then pulling and corona treating to obtain the base film;
[0087] Step S2, weighing raw materials by weight, mixing and stirring the modified hyperbranched polyester prepared in Example 3, polyvinyl pyrrolidone, sodium lauryl sulfate and modified chitosan prepared in Example 3 at 30° C. for 30 minutes, adding aluminum sol and continuing to stir for 60 minutes to form a mixed solution 1; then mixing and stirring the polyacrylic acid resin and deionized water to form a mixed solution 2; finally, slowly adding the mixed solution 2 into the mixed solution 1, and continuing to stir for 50 minutes to obtain a coating solution;
[0088] Step S3, uniformly coating the coating liquid on the surface of the base film, the film layer thickness is 0.2 mm, drying, and rolling up to obtain a PO composite film.
[0089] Comparative Example 1
[0090] This comparative example is a PO composite membrane, which differs from Example 6 in that a nonionic surfactant (polyoxyethylene ether) is used instead of the modified hyperbranched polyester prepared in Example 3, and the rest are the same.
[0091] Comparative Example 2
[0092] This comparative example is a PO composite membrane, which is different from Example 6 in that commercially available chitosan is used instead of the modified chitosan prepared in Example 3, and the rest are the same.
[0093] The PO composite membranes prepared in Examples 4-6 and Comparative Examples 1-2 were subjected to performance tests:
[0094] Contact angle test: immerse the PO composite membrane in 100 mL of water at 60°C, change the water and take a sample every hour, and use a PG-X dynamic and static surface contact angle meter to measure and record the contact angle values of the sample at 0h, 12h, 24h, 3d, 10d, 30d, 60d, and 90d;
[0095] The test results are shown in the following table:
[0096]
[0097] It can be seen from the above table that the PO composite film prepared by the present invention has a lower static contact angle in general. The static contact angle varies greatly in the early range of 0-24 hours, and tends to be stable after 24 hours, indicating that after the coating liquid is coated on the surface of the base film, the static contact angle of the PO composite film can be significantly reduced, so that the surface presents an excellent hydrophilic state and maintains it for a long time, thereby improving the drip anti-fog performance of the PO composite film and reducing the occurrence of water beads and dripping on the PO composite film.
[0098] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A PO composite membrane, characterized in that: The base film is formed by co-extrusion of an inner layer, a sub-outer layer and an outer layer, and the base film is then uniformly coated with a coating liquid; the thickness of the inner layer: the thickness of the sub-outer layer: the thickness of the outer layer in the base film is 1:3-5:1; the inner layer, the sub-outer layer and the outer layer are respectively made of the following raw materials in the following mass percentages: Inner layer: 20%-25% low-density polyethylene, 60%-70% linear low-density polyethylene, 10%-20% antistatic masterbatch, the antistatic masterbatch is made of the following raw materials in mass percentage, namely: 75%-85% low-density polyethylene, 15%-25% antistatic agent and 1%-2% antioxidant are mixed, melted at high temperature and pelletized; Second outer layer: 20-25% low-density polyethylene, 40-70% metallocene polyethylene, 10-20% hydrotalcite masterbatch, the hydrotalcite masterbatch is made of the following raw materials in percentage by mass, namely: 70%-80% low-density polyethylene, 15%-30% hydrotalcite, 1%-2% antioxidant and 2%-4% hindered amine light stabilizer are mixed, melted at high temperature and pelletized; Outer layer: 40-50% metallocene polyethylene, 15-25% high-density polyethylene, 30%-40% antioxidant masterbatch, the antioxidant masterbatch is made of the following raw materials in percentage by mass, namely: 30%-40% low-density polyethylene, 40%-60% linear low-density polyethylene, 1%-2% antioxidant, 3%-6% hindered amine light stabilizer, 2-4% ultraviolet absorber and 1%-3% antistatic agent are mixed, melted at high temperature and pelletized.
2. A PO composite membrane according to claim 1, characterized in that: The coating liquid comprises the following raw materials in parts by weight: 25-35 parts of aluminum sol, 5-8 parts of modified hyperbranched polymer, 2-4 parts of polyvinyl pyrrolidone, 1-3 parts of sodium lauryl sulfate, 5-7 parts of polyacrylate resin, 4-6 parts of modified chitosan, and 45-55 parts of deionized water; The modified hyperbranched polymer is prepared by the following steps: Step A1, adding methyltrimethoxysilane and dimethyldiethoxysilane to an ethanol solution, stirring at a speed of 400-600 rpm for 1.5-2.5 hours, then slowly adding trifluoropropane trimethoxysilane and tetraethyl orthosilicate and continuing stirring for 1-2 hours, adding 10wt% ammonia water and stopping stirring, transferring to a 60°C water bath and standing for 30-50 minutes, centrifuging, washing, and drying to obtain silicone microspheres; Step A2, trimethylolpropane triglycidyl ether and tetrabutylammonium bromide are uniformly mixed in an N,N-dimethylformamide aqueous solution, and then silicone microspheres are added, reacted under nitrogen at 80-90° C. for 3-4 hours, tetrahydrofuran is added and stirred for 10 minutes, washed and dried to obtain a hyperbranched polymer precursor; Step A3, the hyperbranched polymer precursor and sodium hydroxide are mixed evenly in ethanol, dopamine hydrochloride is added and stirred to react for 2-3 hours, and the mixture is distilled under reduced pressure, filtered, washed and dried to obtain a modified hyperbranched polymer.
3. A PO composite membrane according to claim 2, characterized in that: In step A1, the dosage ratio of methyltrimethoxysilane, dimethyldiethoxysilane, trifluoropropanetrimethoxysilane, tetraethyl orthosilicate, ethanol solution and ammonia water is 0.05-0.15 mol: 0.03-0.06 mol: 0.01-0.03 mol: 0.08-0.12 mol: 200 mL: 1-3 mL, and the volume ratio of ethanol and deionized water in the ethanol solution is 1:
1.
4. A PO composite membrane according to claim 2, characterized in that: In step A2, the dosage ratio of trimethylolpropane triglycidyl ether, tetrabutylammonium bromide, N,N-dimethylformamide aqueous solution, silicone microspheres and tetrahydrofuran is 0.01-0.03 mol: 0.0005-0.0015 mol: 100 mL: 1-3 g: 10 mL, and the volume ratio of N,N-dimethylformamide and deionized water in the N,N-dimethylformamide aqueous solution is 4:
1.
5. A PO composite membrane according to claim 2, characterized in that: In step A3, the usage ratio of the hyperbranched polymer precursor, sodium hydroxide, ethanol and dopamine hydrochloride is 1-3 g: 0.01-0.02 g: 50 mL: 0.5-2 g.
6. A PO composite membrane according to claim 2, characterized in that: The modified chitosan comprises the following steps of preparation: Step B1, adding chitosan to a 3wt% glacial acetic acid solution and stirring for 30min, adding 10mL of anhydrous ethanol and stirring for 10min, heating to 35-45°C, adding 2-4wt% glyoxal solution and stirring for 1-2h, centrifuging and washing, redispersing in 100mL of anhydrous ethanol, adding N,N-dimethylethylenediamine, and reacting at 40-50°C for 2-3h, centrifuging and drying to obtain pre-treated chitosan; Step B2, disperse the pretreated chitosan in ethanol, heat to 45°C, slowly drop 1-chlorododecane, stir to react for 8-12h, let stand for 12h, centrifuge, rotary evaporate, and dry to obtain modified chitosan.
7. A PO composite membrane according to claim 6, characterized in that: In step B1, the usage ratio of chitosan, glacial acetic acid solution, glyoxal solution and N,N-dimethylethylenediamine is 1-3 g: 10-20 mL: 10-20 mL: 0.5-2 mL.
8. A PO composite membrane according to claim 6, characterized in that: In step B2, the usage ratio of pre-treated chitosan, ethanol and 1-chlorododecane is 1-3 g:50 mL:0.5-2 mL.
9. The method for preparing a PO composite membrane according to claim 1, characterized in that: The following steps are involved: Step S1, weighing the raw materials according to the mass percentage, respectively putting the raw materials of the outer layer, the sub-outer layer and the inner layer of the base film into the corresponding production barrels, blow-molding by a three-layer co-agent blow-molding unit, and then pulling and corona treating to obtain the base film; Step S2, weighing the raw materials by weight, mixing and stirring the modified hyperbranched polyester, polyvinyl pyrrolidone, sodium lauryl sulfate and modified chitosan at 25-30° C. for 30 minutes, adding aluminum sol and continuing to stir for 40-60 minutes to form a mixed solution 1; then mixing and stirring the polyacrylic acid resin and deionized water to form a mixed solution 2; finally, slowly adding the mixed solution 2 to the mixed solution 1, and continuing to stir for 30-50 minutes to obtain a coating solution; Step S3, uniformly coating the coating liquid on the surface of the base film, with a film thickness of 0.1-0.2 mm, drying, and rolling up to obtain a PO composite film.
Citation Information
Patent Citations
Three-layer co-extruded high-heat-preservation light-conversion PO film
CN108099326A
PO film coating liquid and preparation method thereof
CN112280335A
Cited By
PO film with good cooling effect in summer and preparation method thereof
CN120966070A